Invasive and Non-Invasive Human Salmonellosis Cases Admitted between 2015 and 2021 in Four Suburban Hospitals in the Metropolitan Area of Milan (Italy): A Multi-Center Retrospective Study - Gabriele Pagani; Marco Parenti; Marco Franzetti; Laura Pezzati; Francesco Bassani; Bianca Osnaghi; Laura Vismara; Claudia Pavia; Paola Mirri; Stefano Rusconi (Pathogens, 2023)
Non-Typhoidal Salmonellas (NTSs) are diffused worldwide. In Italy, more than 3500 cases are notified each year, but despite this, data about salmonellosis are scarce. Our multi-center, retrospective, descriptive study selected 252 patients with positive cultures for Salmonella spp. (feces 79.8%, blood 8.7%, feces and blood 7.5%), aiming to describe the epidemiological and clinical characteristics of this population. Bacteremic infections constituted 16.3% (41/252) of patients. Extreme ages (≤12 and ≥65 years old) accounted for 79.7%, but only elder ages were strongly associated with bacteremic infections (aOR 5.78). Invasive infections had a 7-fold higher mortality rate than non-invasive disease (9.8% vs. 1.4%, p = 0.013), with an overall rate of 2.8%. The two more represented serogroups were O:4 (52.8%) and O:9 (22.2%). The O:9 serogroup was strongly associated with a higher frequency of invasive infection (aOR 2.96, 95% CI 1.17–7.63). In particular, S. napoli, an emerging serovar in Europe, accounted for 31.7% of bacteremic infections and only 9.5% of non-bacteremic ones (p < 0.001). Antibiotic microbial resistance (AMR) observed a steep increasing trend and was detected in 60.4% of cases (122/202): amoxicillin/clavulanate, ampicillin, and gentamicin were most commonly involved (26.7%, 21.8%, 14.3%, respectively), while TMP/SMX, ciprofloxacin, and ceftriaxone were <10%. Resistance was, in general, less common in the O:9 serogroup, while amikacin resistance was significantly more common. Factors associated with an MDR Salmonella acquisition were time (OR 1.37 per year more), O:4 serogroup (OR 2.67), and being a woman (OR 2.11). The most frequent symptoms were diarrhea (90.5%) and fever (81.7%). In conclusion, our study highlights a high burden of NTS infections, leading to severe or fatal outcomes in frail patients. Furthermore, AMR shows an increasing trend with a concerning high prevalence of cephalosporine resistance compared to the rest of Europe.